2021
DOI: 10.6023/cjoc202011012
|View full text |Cite
|
Sign up to set email alerts
|

Silver Selenide as the Novel Catalytic Material for Alcohol Oxidation

Abstract: By calcining selenium powder and silver powder at 150 ℃ under N2 protection, the novel material silver selenide (Ag/Se) could be easily fabricated. It possessed very strong oxygen carrier features and could activate the molecular oxygen to achieve the catalytic oxidation reactions. In this work, the Ag/Se-catalyzed alcohol oxidation reactions were investigated to afford a novel clean method for the synthesis of carbonyls. It could be applied for the oxidation reactions of primary and secondary alcohols, and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 40 publications
3
7
0
Order By: Relevance
“…It was found that although the reaction catalyzed by the mixture of silver and selenium with their molar ratio at 1 : 10 led to 5 in poor yield, the Ag/Se material that was prepared via the calcination of silver and selenium showed obviously better catalytic activity, and the reaction catalyzed by Ag/Se could produce 5 in 42 % yield (Scheme 2, Runs 4 vs. 3). The phenomena demonstrated that the combination of silver and selenium during the calcination process could promote their catalytic activities for oxidation reaction, which was in accordance with the literature report [16] …”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…It was found that although the reaction catalyzed by the mixture of silver and selenium with their molar ratio at 1 : 10 led to 5 in poor yield, the Ag/Se material that was prepared via the calcination of silver and selenium showed obviously better catalytic activity, and the reaction catalyzed by Ag/Se could produce 5 in 42 % yield (Scheme 2, Runs 4 vs. 3). The phenomena demonstrated that the combination of silver and selenium during the calcination process could promote their catalytic activities for oxidation reaction, which was in accordance with the literature report [16] …”
Section: Resultssupporting
confidence: 92%
“…On the basis of the above experimental results as well as the literature reports, [16,21–26] a plausible mechanism was supposed (Scheme 4). First, selenium as a non‐metal element may lead to the low valent selenium species in Ag/Se [16] .…”
Section: Resultssupporting
confidence: 62%
See 2 more Smart Citations
“…We also report the green synthesis of silver nanoparticles (Ag NPs) using Echium amoenum ( E. amoenum ) extract. Recently, silver nanoparticles have been used as a suitable catalyst in many reactions, including the oxidation of alcohol, 21 oxidation of styrene, 22 synthesis of β-enaminones, 23 preparation of tetrazoles, 24 oxidation of phenylsilanes to silanols 25 and synthesis of propargylamines. 26 We found that our Ag NPs produce our desired compounds in high yields (80–97%) with excellent recovery and a simple work-up procedure.…”
Section: Introductionmentioning
confidence: 99%